Whole-genome sequencing of Alcaligenes sp. strain MMA: insight into the antibiotic and heavy metal resistant genes - Sodhi, Kushneet Kaur; Singh, Chandra Kant; Kumar, Mohit; Singh, Dileep Kumar (Frontiers in Pharmacology, 2023)
Introduction: A wide range of pollutants, including the likes of xenobiotics, heavy metals, and antibiotics, are characteristic of marine ecosystems. The ability of the bacteria to flourish under high metal stress favors the selection of antibiotic resistance in aquatic environments. Increased use and misuse of antibiotics in medicine, agriculture, and veterinary have posed a grave concern over antimicrobial resistance. The exposure to these heavy metals and antibiotics in the bacteria drives the evolution of antibiotic and heavy metal resistance genes. In the earlier study by the author Alcaligenes sp. MMA was involved in the removal of heavy metals and antibiotics. Alcaligenes display diverse bioremediation capabilities but remain unexplored at the level of the genome. Methods: To shed light on its genome, the Alcaligenes sp. strain MMA, was sequenced using Illumina Nova Seq sequencer, which resulted in a draft genome of 3.9 Mb. The genome annotation was done using Rapid annotation using subsystem technology (RAST). Given the spread of antimicrobial resistance and the generation of multi-drug resistant pathogens (MDR), the strain MMA was checked for potential antibiotic and heavy metal resistance genes Further, we checked for the presence of biosynthetic gene clusters in the draft genome. Results:Alcaligenes sp. strain MMA, was sequenced using Illumina Nova Seq sequencer, which resulted in a draft genome of 3.9 Mb. The RAST analysis revealed the presence of 3685 protein-coding genes, involved in the removal of antibiotics and heavy metals. Multiple metal-resistant genes and genes conferring resistance to tetracycline, beta-lactams, and fluoroquinolones were present in the draft genome. Many types of BGCs were predicted, such as siderophore. The secondary metabolites of fungi and bacteria are a rich source of novel bioactive compounds which have the potential to in new drug candidates. Discussion: The results of this study provide information on the strain MMA genome and are valuable for the researcher in further exploitation of the strain MMA for bioremediation. Moreover, whole-genome sequencing has become a useful tool to monitor the spread of antibiotic resistance, a global threat to healthcare.